Identification of small molecules that mitigate vincristine‐induced neurotoxicity while sensitizing leukemia cells to vincristine. Issue 4 (31st May 2021) - Diouf, Barthelemy; Wing, Claudia; Panetta, John C.; Eddins, Donnie; Lin, Wenwei; Yang, Wenjian; Fan, Yiping; Pei, Deqing; Cheng, Cheng; Delaney, Shannon M.; Zhang, Wei; Bonten, Erik J.; et al.
Abstract: Vincristine (VCR) is one of the most widely prescribed medications for treating solid tumors and acute lymphoblastic leukemia (ALL) in children and adults. However, its major dose‐limiting toxicity is peripheral neuropathy that can disrupt curative therapy. Peripheral neuropathy can also persist into adulthood, compromising quality of life of childhood cancer survivors. Reducing VCR‐induced neurotoxicity without compromising its anticancer effects would be ideal. Here, we show that low expression of NHP2L1 is associated with increased sensitivity of primary leukemia cells to VCR, and that concomitant administration of VCR with inhibitors of NHP2L1 increases VCR cytotoxicity in leukemia cells, prolongs survival of ALL xenograft mice, but decreases VCR effects on human‐induced pluripotent stem cell‐derived neurons and mitigates neurotoxicity in mice. These findings offer a strategy for increasing VCR's antileukemic effects while reducing peripheral neuropathy in patients treated with this widely prescribed medication.